Sacral Reflex Characteristics of Patients with Multiple System Atrophy - Zhifang Pan; Xueming Zhang; Xun Wang; Binbin Deng; Wanli Zhang; Huanjie Huang (Parkinson's Disease)
Objectives. To observe and analyze the parameters of the sacral reflex and pudendal nerve somatosensory evoked potential (SSEP) in patients with multiple system atrophy (MSA) with respect to factors such as age, disease course, and subtype and provide evidence for the clinical diagnosis of MSA. Materials and Methods. A total of 51 MSA patients and 30 healthy controls were selected from the First Affiliated Hospital of Wenzhou Medical University from May 2013 to November 2015. Electrophysiological sacral reflex detection and SSEP detection were performed using the Keypoint EMG/EP system. The extraction rate, latency, and amplitude of the sacral reflex and SSEP in the MSA group and control group were compared. Results. The sacral reflex latency and amplitude in patients with MSA were statistically different from those of the healthy controls. The latency of sacral reflex increases with the prolongation of the disease course, and the amplitude and initiation rate decrease with the prolongation of the disease course. There was no significant difference in sacral reflex latency and amplitude between MSA patients of different ages and subtypes. There was no significant difference in the latency or amplitude of SSEP between the MSA group and healthy control group. Conclusions. The latency of sacral reflex increases with the prolongation of the disease course, and the amplitude and extraction rate decrease with the prolongation of the disease course. There was no significant difference in the parameters of sacral reflex between young MSA patients and elderly patients. And there was no statistically significant difference between MSA-P subtypes and MSA-C subtypes. This trial is registered with ISRCTNCR2009041.